2005
DOI: 10.1093/rheumatology/keh481
|View full text |Cite|
|
Sign up to set email alerts
|

Efficacy of alendronate, a bisphosphonate, in the treatment of AVN of the hip. A prospective open-label study

Abstract: Alendronate reduces pain, improves function and retards AVN progression. Early surgical intervention can be avoided in most patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
110
0
2

Year Published

2006
2006
2017
2017

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 210 publications
(114 citation statements)
references
References 19 publications
2
110
0
2
Order By: Relevance
“…Bisphosphonates reduce pain, extension of BMLs and improve functional outcomes in benign condition like osteonecrosis, 51,52 regional transient osteoporosis, 53 enthesopathy in spondyloarthritis 54 and regional pain syndromes. 55 Most of the studies have been open label or interventional, but for osteonecrosis and regional pain syndrome significant effects have been demonstrated in randomised prospective trials.…”
Section: Pharmaceutical Optionsmentioning
confidence: 99%
“…Bisphosphonates reduce pain, extension of BMLs and improve functional outcomes in benign condition like osteonecrosis, 51,52 regional transient osteoporosis, 53 enthesopathy in spondyloarthritis 54 and regional pain syndromes. 55 Most of the studies have been open label or interventional, but for osteonecrosis and regional pain syndrome significant effects have been demonstrated in randomised prospective trials.…”
Section: Pharmaceutical Optionsmentioning
confidence: 99%
“…Medical therapies as well as nonpharmacological therapies, including modified weight bearing, hyperbaric oxygen and extracorporeal shock wave therapy, have been the subject of multiple investigations, including several prospective studies. 18,[32][33][34][35][36][37][38][39][40][41][42][43][44][45][46][47] Bisphosphonates have received specific attention owing to their known effect of decreasing osteoclast-mediated bone turnover that theoretically could prevent subchondral bone collapse. A randomized controlled trial assessing 54 hips reported significantly lower rates of disease progression and need for arthroplasty in patients treated with bisphosphonates for 2 months.…”
Section: Discussionmentioning
confidence: 99%
“…Genel olarak, yapılan çalışmalarda, bifosfonatların ağrı, fonksiyon ve femur başı şeklinin korunmasına olumlu katkıları olduğu belirtilmektedir. [23,[25][26][27][28] LCPD tedavisinde bifosfonat kullanımı ile ilgili çe-kinceler arasında; ilacın osteonekrotik bölgeye yetersiz dağılımı, anabolik etkisinin olmaması, kemiğin mekanik özellikleri üzerine olumlu etkisinin olmaması, bü-yümekte olan çocuğun iskelet sistemine uzun dönem etkisinin bilinmemesi sayılmaktadır. Avasküler bir kemik bölgesinde, ilacın lokal miktarının ne olacağı bilinmemektedir.…”
Section: Anti̇rezorpti̇f Tedavi̇unclassified